Maduración de ovocitos y desarrollo de embriones bovinos cocultivados en monocapas celulares - Maruri, Alejandro (2018)
During the twentieth century, the introduction of innovative reproductive\nbiotechnologies in cattle production has allowed a breakthrough in this field. The embryo transfer produced by in vitro fertilization (IVF) increased significantly and\nin 2013 reached a global record high of 42% of transferred embryos. However, despite scientific efforts to optimize systems for in vitro production (IVP), the culture conditions remain suboptimal. Thus, the performance and quality of\nembryos are lower than those produced in vivo thereby generating higher early embryonic losses that negatively affect production.\nCoculture with somatic cells could improve suboptimal conditions and\npromote embryonic development through the production of mitogenic compounds\nand substances that promote cell differentiation. Also, through detoxifying and modifying embryotoxins concentrations and energy substrates. Besides, the\nstudy of coculture systems would provide valuable information about the\nrequirements for early embryonic development, biochemistry of somatic cells and their interaction with the embryo. The aim of this thesis is to optimize the bovine embryo production from IVF, using systems of coculture with granulosa and luteal cells from bovine, to\nincrease yield and/or quality of blastocysts produced. The effect of two coculture\nsystems with bovine granulosa cells: granulosa cells line 1 (BGC-1) and\ngranulosa cells from passage 1 after primary culture (CGB-1), on in vitro\nmaturation were assessed. Similarly, unpurified cells from a primary culture of\nbovine corpus luteum were used but the results were inconclusive. Furthermore,\nthe effect of a coculture system with purified bovine luteal cells of passage 1\n(CLB-1) during early embryonic development was evaluated. The presence of\nBGC-1 showed no beneficial effect on oocyte nuclear maturation compared to\nthe control group (without cells). Varying maturation rates were observed, and in\nmost cases, meiotic resumption was inhibited. By employing an alternative model with CGB-1 significantly increases the nuclear maturation rates (85%) compared\nto the control (70%). However, there were no differences in Annexin V-FITC rate (determination for early apoptosis) or dead rate in oocyte between groups. Also, late apoptosis (TUNEL assay) was evaluated and there were no differences\nbetween groups (CGB-1: 1.12% vs. control 1.33%). After IVM, oocyte levels of\nreactive oxygen species (ROS) were determined using DCHFDA assay and it\nshowed a significant increase in coculture group with CGB-1. As an indirect\nassessment parameter of oocyte cytoplasmic maturation, IVF assays were\nperformed. In this case, the control group received the gonadotropins. The\ncleavage rate was determined at 48 h post-IVF and was similar in both groups (CGB-1: 80.5% vs. control: 79.4%). However, blastocysts rate was significantly lower in control than the coculture (CGB-1: 14% vs. control: 25.6%).\nThe embryo coculture with CLB-1 was performed during the first 48 h of in\nvitro culture (IVC). The CLB were previously isolated and purified by differential\ncentrifugation on a discontinuous Percoll? density gradient, and the purity was determined by immunocytochemistry (ICC) using antibodies against 3?-HSD (enzyme that catalyzes progesterone biosynthesis from pregnenolone). All the\ncells selected (fractions 5 and 6 of the Percoll? gradient) were positive to 3?HSD. Nile red dye was used to detect cytoplasmic lipid droplets and all the cells\nassessed were positive indicating steroidogenic activity preserved. On the other hand, cells from passage 1 without selection showed 80.6% ± 7,02 of positive cells. This coculture system modified the kinetic of embryo development respect to a conventional system that not uses cells (control). A significantly increase in blastocyst rate (CLB-1: 50% vs. control: 30%) and stage 6-blastocyst rate (CLB1: 37% vs. control: 24%) was observed. The ROS level was measured in day 2- embryos and was significantly higher in the coculture. Furthermore, the detection of the proliferation antigen Ki-67, as an early marker of embryo quality, was proposed. The cell proliferation rate and the mean number of blastomeres were\ndetermined in day 2-embryos using immunofluorescence for Ki-67 and Hoechst\n33342 staining. The cell proliferation rate in embryos cultured with CLB-1 was\nsignificantly higher than the control but there were no differences in a mean\nnumber of blastomeres. Late apoptosis (TUNEL assay) was assessed in blastocysts and the rate of apoptotic blastomeres was lower in coculture with CLB-1 than the control (4.10% vs. 10.90%). In conclusion, the coculture system with BGC-1 is not an alternative to\noptimize PIV of the bovine embryo. On the other hand, the coculture with CGB-1\nshowed a positive effect on nuclear maturation but their use was not superior\nregarding efficiency about traditional PIV system. The effects of this coculture\nwere evident delayed, and the lower yield may be associated with an increased level of ROS in oocytes. Finally, the use of CLB-1 in coculture during early embryo\ndevelopment showed a significant embryotrophic effect with high blastocyst yield of a better quality, thereby optimizing the PIV of the bovine embryo.\n